Identity-based key-exposure resilient cloud storage public auditing scheme from lattices - Zhang, Xiaojun (2021)
With the rapid development of cloud auditing services, key exposure has been highlighted as a serious security issue. Using the exposed private key of a client, cloud servers can forge previous auditing proofs to cheat auditors. To date, a few pairing-based cloud storage auditing schemes addressing key exposure have been proposed. However, they are not secure from quantum attacks, and they rely on public key infrastructure (PKI), which involves complex certificate management. In this paper, we propose an efficient identity-based key-exposure resilient public auditing scheme from lattice assumptions in cloud storage. Our scheme is not only quantum-resistant, but eliminates the need to establish a PKI. We employ lattice basis delegation technique to update a client's private key flexibly, keeping the private key size constant. Based on the hardness of lattice assumptions, we prove the forward security of storage correctness guarantee against malicious cloud servers in detail, and that the proposed scheme preserves privacy against curious auditors. Furthermore, we conduct a performance comparison to demonstrate that our scheme is much more efficient and practical for post-quantum secure cloud storage.